Arabic Language Learning Method in Madrasah Diniyah of Ar-Rohmah Putri International Islamic Boarding School Malang : Metode Pembelajaran Bahasa Arab di Madrasah Diniyah Sekolah Islam Asrama Internasional Ar-Rohmah Putri Malang - Rahmah , Nabilah Nailah; Ammar, Farikh Marzuki (Indonesian Journal of Education Methods Development, 2025)
General Background: Arabic language learning in Islamic educational institutions requires structured pedagogical approaches to achieve communicative competence and mastery of linguistic rules. Specific Background: Madrasah Diniyah Ar-Rohmah Putri International Islamic Boarding School Malang implements structured Arabic instruction as a compulsory subject supported by institutional language policies and intensive programs. Knowledge Gap: Although various studies discuss Arabic teaching methods, limited research documents the applied instructional models in Madrasah Diniyah Ar-Rohmah Putri, particularly at Marhalah Dua level. Aims: This study aims to identify and describe the Arabic language learning methods applied in Marhalah Dua at the institution. Results: Using a descriptive qualitative field research design through interviews, observation, and documentation, the findings indicate that instruction applies the Direct Method for daily communicative practice and vocabulary memorization, supported by Arabic Night activities, alongside the Eclectic Method integrating speaking, reading, writing, and grammatical instruction including nahwu and shorof exercises. Novelty: The study provides contextual documentation of the combined implementation of Direct and Eclectic Methods within a structured boarding school environment. Implications: The findings contribute practical insights for Islamic educational institutions seeking structured and varied Arabic instructional strategies aligned with communicative and grammatical objectives. Keywords: Arabic Learning Methods, Direct Method, Eclectic Method, Madrasah Diniyah, Qualitative Field Research Key Findings Highlights: Classroom instruction integrates structured vocabulary drills with communicative practice activities. Boarding school language policy reinforces daily spoken Arabic usage. Grammar instruction is systematically combined with dialogue-based exercises.